Value of social network for development of rural Malay herbal entrepreneurship in Malaysia - Paul, Kamal Chandra; Hamzah, Azimi; Abu Samah, Bahaman; Ismail, Ismi Arif; D'Silva, Jeffrey Lawrence (Elsevier, 2014)
The purpose of the study was to explore the value of social networking among rural Malay herbal entrepreneurs in Malaysia. It was a qualitative case study research and in-depth interview was used to collect data from ten rural Malay herbal entrepreneurs and conducted in MAHA (Malaysian Agriculture, Horticulture and Agrotourism). The finding showed that majority of the rural Malays herbal entrepreneurs are lagging behind relatively to other ethnic groups in Malaysia due to poor networking. It is also suggested that rural Malay herbal entrepreneurs need to immediately develop their own network skills through government, family members, relatives, friends and other form of support groups.